Pengembangan Daya Tarik Wisata Edukatif Museum Basoeki Abdullah - Rizki Nurul Nugraha; Alisya Nur Insani (Peneliti.net, 2023)
This study aims to determine the attractiveness of the Basoeki Abdullah museum as an educational tour, the Basoeki Abdullah museum exhibits various works of his paintings which are already worldwide. This research can have a good impact by raising and introducing the Basoeki Abdullah Museum to the public that this museum is not only visited solely for content needs but can be an educational tour and add insight into knowledge about painting, so that it can be visited by all groups. This study used a qualitative research method based on the data collection stage and continued with observations and interviews and was strengthened by a SWOT analysis. This research shows that the concept of collaboration can build interest in educational tourism among the wider community.